Kontribusi Kreativitas Siswa dan Fasilitas Labor Terhadap Hasil Belajar Mata Diklat Keterampilan Komputer dan Pengelolaan Informasi (KKPI) Siswa Kelas X di SMK Negeri 1 Tilatang Kamang - Feri Febrianto; Zulwisli Zulwisli; Sukaya Sukaya (Universitas Negeri Padang, 2014)
This research is purposed to reveal scales of student’s creativity contribution and laboratorium of facility grade for computer and information management skills subject at X class SMKN 1 Tilatang Kamang. The type of this research is descriptive correlation. Populations in this research are 164 students, and samples are amount to 62 students of X class SMKN 1 Tilatang Kamang, school of year 2012/2013. Samples are taken by simple random sampling technique. Data were collected by questionnaire and documentation. Data analysis technique in this research is Pearson product moment and multiple-correlation. Results from data analysis claimed that there are contributions from learning motivation and learning environment for student’s grade of computer and information management skills subject at X class SMKN 5 Padang, as follow: (1) student’s creativity gives contribution to student’s grade by 14,13%, (2) laboratorium of facility gives contribution to student’s grade by 20.09%, (3) student’s creativity together with laboratorium of facility give contribution to student’s grade by 27,98%. This research suggest that student’s student’s creativity and laboratorium of facility give contribution to student’s grade.Keywords: student’s creativity, laboratorium of facility, student’s grade, descriptive correlation, simple random sampling.